2016
DOI: 10.1177/1468017316654346
|View full text |Cite
|
Sign up to set email alerts
|

Australian social work research on ageing and aged care: A scoping review

Abstract: Little is known about the quantity, nature and range of Australian social work research on ageing and aged care. This scoping review involved a comprehensive search of seven online bibliographic databases. The review identified 108 peer-reviewed journal articles, published between January 2007 and June 2014, that reported Australian social work research on ageing and aged care. Findings: The average number of authors per paper was 2.10 with most social work researchers co-authoring papers with non-social worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Although possibly included in multidisciplinary and health research centres, authors from social work and social policy, and other social sciences, including demography, economics and statistics, were a small minority (5%), and even fewer came from environmental, design and technology disciplines (3%). While the question arises as to whether researchers from these fields publish in discipline‐specific journals, the recent scoping review of Australian social work research on ageing and aged care suggests that this is not the case . That review, covering 53 journals over the period 2007–2014, found that the AJA led, with 13% of the 108 articles identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although possibly included in multidisciplinary and health research centres, authors from social work and social policy, and other social sciences, including demography, economics and statistics, were a small minority (5%), and even fewer came from environmental, design and technology disciplines (3%). While the question arises as to whether researchers from these fields publish in discipline‐specific journals, the recent scoping review of Australian social work research on ageing and aged care suggests that this is not the case . That review, covering 53 journals over the period 2007–2014, found that the AJA led, with 13% of the 108 articles identified.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, while the present review has been limited by its focus on the “who” and “where” of ageing research, its short time span and restriction to publication in the AJA, the findings provide grounds for further analysis of the content, methods and rationales of ageing research published in a wider array of journals to answer the “what,” “how” and “why” questions. A comprehensive account could be compiled through a large‐scale single review or a series of co‐ordinated scoping reviews or meta‐analyses by major fields, along the lines of social work review by Hughes et al, or by research designs; a recent synthesis review of international longitudinal qualitative research in gerontology points to the value of a similar account of the output of Australian longitudinal studies over the last two decades as a foundation for further research, whether longitudinal or cross‐sectional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they aim to demonstrate the advantages that could be gained from the critical analysis of positive ageing, especially because government institutions and representatives on all levels seem to prefer such ageing policy, which tries to subordinate the social needs of elderly to the needs of economic growth and labour market (Hughes et al, 2016).…”
Section: Theoretical Questions Regarding Ageing Labour Force and Its mentioning
confidence: 99%
“…practitioner-academic research partnerships to help build the stock of knowledge about what works in social work practice (e.g., Joubert & Hocking, 2015). Nonetheless, there remains a dearth of service user-led social work research in Australia (e.g., Hughes, Bigby, & Tilbury, 2016). Inclusion of service users as "research end user" panel members for the ERA assessment of engagement and impact may prompt some change in this direction.…”
mentioning
confidence: 99%